Functional Outcome of Femoral Neck Fracture Osteosynthesis by Biplane Double Supported Screw Fixation Method (BDSF) (Medicine Today, 2026)
Background with Objective: Treatment of fracture neck of femur varies according to patient’s age, fracture pattern and time of presentation. There are various method of fixation technique like inverted triangle, triangle and diamond shape. The aim of this study was to evaluate functional outcome in fracture neck of femur fixation by biplane double supported screw fixation (BDSF) method. Materials and Methods: This was a single group prospective hospital based clinical trial and was conducted in the Department of Orthopedic Surgery in Chittagong medical college hospital for a period of one and half year from July 2018 to July 2020. Sample size was 30 with (AO /OTA-31B) fracture as per set criteria treated with BDSF enrolled through inclusion and exclusion criteria. Depending on the overall functional outcome patients were grouped as having excellent to good outcome and fair to poor outcome according to Harris hip score. Patients were followed up for 12 months. Result: Functional outcome at the final follow-up most of the patients, 23 (82.1%) had excellent outcome. Both good and poor outcome were in 02 (7.1%) and fair outcome was in only 01 (3.6%) patients respectively according to Harris Hip Score (1969). Conclusion: The achieved results with the BDSF method in terms of fracture consolidation are far more successful than the results with conventional fixation methods.The BDSF method ensures reliable fixation, early rehabilitation and excellent long-term outcomes.Medicine Today 2026, Vol.38 (1): 46-49